Front Cover: High‐Energy Nickel‐Cobalt‐Aluminium Oxide (NCA) Cells on Idle: Anode‐ versus Cathode‐Driven Side Reactions (Batteries & Supercaps 6/2021). Issue 6 (11th May 2021) - Zülke, Alana; Li, Yi; Keil, Peter; Burrell, Robert; Belaisch, Sacha; Nagarathinam, Mangayarkarasi; Mercer, Michael P.; Hoster, Harry E.
Abstract : The Front Cover illustrates how state of charge (SoC) influences the capacity fade of a widely employed automotive Li‐ion battery chemistry when idle, e.g., when EVs are parked. The chemical degradation is revealed to be aggravated when devices are kept at around 80 % SoC. More information can be found in the Article by A. Zülke and co‐workers .